2020
DOI: 10.1007/s00170-020-06219-4
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced softening analysis of a hardened aluminum alloy by physical simulation

Abstract: The study focuses on the analysis of the softening effects of the work-hardened aluminum alloy sheets EN AW 5754 H32 1.5 mm thick, through the physical simulation of thermal cycles induced in the material by laser heat treatments (LHTs). A numerical-experimental approach was implemented to define the laser thermal cycles and to subsequently reproduce them on the GleebleTM 3180 physical simulator. The obtained softening was measured by microhardness and metallographic analysis tests. For the definition of laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Preliminary tests have shown that a cooling rate of 25 K/s is enough to characterize the material in austenitic field even at the lowest temperature and strain rate investigated. The respect of this cooling rate without the use of forced air has been obtained performing the specimen design with a FE model developed in COMSOL Multiphysics [12].…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary tests have shown that a cooling rate of 25 K/s is enough to characterize the material in austenitic field even at the lowest temperature and strain rate investigated. The respect of this cooling rate without the use of forced air has been obtained performing the specimen design with a FE model developed in COMSOL Multiphysics [12].…”
Section: Methodsmentioning
confidence: 99%
“…Since these are rapid thermal cycles, to satisfy the cooling rate during Gleeble tests, a tapered specimen was adopted. The geometry of specimens was defined thanks to optimization of the length and width of the shaped area studied in the previous work [12]. Physical simulation tests were carried out on the tapered specimens that were subjected to the subsequent micro-hardness test, and on notched specimens that were subjected, instead, to the subsequent tensile test.…”
Section: Methodsmentioning
confidence: 99%
“…The results acquired from the thermocouples were used to estimate the peak temperature profile thanks to a thermo-electric, 3D, transient, finite-element model developed in COMSOL Multiphysics [12]. The FE model couples the thermal and electrical fields.…”
Section: Physical Simulation Of Lhtmentioning
confidence: 99%
See 2 more Smart Citations